Accelerated partial breast irradiation in early stage breast cancer - Paulina E. Galavis; Camille Hardy Abeloos; Pine C. Cheng; Christine Hitchen; Allison McCarthy; Juhi M. Purswani; Bhartesh Shah; Sameer Taneja; Naamit K. Gerber (Frontiers in Oncology, 2022)
Accelerated partial breast irradiation (APBI) is increasingly used to treat select patients with early stage breast cancer. However, radiation technique, dose and fractionation as well as eligibility criteria differ between studies. This has led to controversy surrounding appropriate patients for APBI and an assessment of the toxicity and cosmetic outcomes of APBI as compared to whole breast irradiation (WBI). This paper reviews existing data for APBI, APBI delivery at our institution, and ongoing research to better define patient selection, treatment delivery, dosimetric considerations and toxicity outcomes.